i need help. i cant seem to get it =[? Topic: i need help. i cant seem to get it =[?
June 27, 2019 / By Andriana
Question: okay now i have some questions for my homework... don't say im just trying to get answer im not i don't just want answers i want to understand it im trying but i cant get it so i have a couple problems out of my worksheet and i was wonwondering someone could do them step by step so i could understand it 5x + 3 = 2x + 15 5x + 2 = x - 6 6x - 8 + 2x - 5 = 7 - 2x 9(x + 2) = 3(x - 2) 5(x + 4) = 7(x - 2) anything helps :) thank you guys soo much you always help me out from pets..odds and ends to math homeworks lol i love yahoo answrs :) thank you guys so much im gonna go look all this stuff up you guys are giving me and figure it out btw i didnt wnat people on yahoo answers to do it for me lady i just wanted some help in the right direction i posted enough problem to get an understanding... im not just trying to get someone eles to do it..i need to learn it so i can pass lol Best Answers: i need help. i cant seem to get it =[? Whitney | 1 day ago
You basically have two kinds of problems. The first few involve grouping like terms, then simplifying . 5x + 3 = 2x + 15 group all the x terms and all of the numbers 5x-2x = 15-3 To move the positive 2x from one site to the other subtract the 2x from both sides. That gets rid of the 2x from the right. Do the same thing with the positive 3 , subtract from both sides. Then simplify. 3x=12. Then divide both sides by 3. x=4. Result x=4. The bottom two problems have an additional step: First multiply the terms inside the parenthesis by the number on the outside. 9(x+2)=3(x-2) becomes 9x+18= 3x-6 now group terms 9x-3x= -18-6 ( we subtracted like terms from both sides) 6x=-24 x=-4
👍 130 | 👎 1
Did you like the answer? i need help. i cant seem to get it =[? Share with your friends Sander
umm r u doing algerbra? if u r maybe the 'x' resembles a number or maybe u shud ask ur math teacher 4 help? anyway, you've confused me lol
👍 50 | 👎 -6 Nandy
5x + 3 = 2x + 15 lets get the x's on one side and the numbers on the other by 5x + 3 + - 3 = 2x + 15 + -3 see we subtracted 3 from both sides 5x = 2x + 15 - 3 which equals 5x = 2x + 12 now lets get the x's on one side 5x + -2x = 2x + -2x + 12 just adding a negative, same as subtracting 3x = 12 because you just subtract the whole number part 3x/3 = 12/3 which says 3x divided by 3 equals 12 divided 3, same on both sides again x = 4 because 3 divided by 3 equals 1 and 1 times any number is equal to that number. To check it we will plug in 4 for the x in the equation. (5 x 4) + 3 = (2 x 4) + 15 (20) + 3 = (8) + 15 23 = 23 must be right! 5x + 2 = x - 6 remember that subtraction is the same as adding a negative number so that means.... 5x + 2 = x + -6 now lets get the x's on one side again 5x + 2 + -2 = x + -6 + -2 applying -2 to both sides 5x = x + -6 + -2 which equals 5x = x + -8 because negative numbers are just like positive numbers if they are the same sing in addition. Now lets get the x's together 5x + -1x = 1x + -1x + -8 because x is equal to 1x since 4x = -8 got rid of the 1x on the right side and subtracted on the left 4x/4 = -8/4 divide both sides by 4 to get just 1x x = -2 To check it we will plug in -2 for x in the equation (5 x -2) + 2 = (1 x -2) + -6 (-10) + 2 = (-2) + -6 because a negative x a positive is negative -8 = -8 must be right again! I'll leave the others for someone else. I'll check back later if no one answers it for you.
👍 50 | 👎 -13 Kenton
I am not going to answer them all for you but I will show you how to work out 1 and you should then be able to do 2. Then Ill do 3 and 5 and you should be able to follow the same method to do 4. 1. 5x + 3 = 2x + 15 The aim is to get x one side and all the rest of the numbers on the other side. This will give you the value of x as in x = ? 5x + 3 = 2x + 15 move the three to the right by subtractiving it from both sides 5x = 2x + 15 - 3 5x = 2x + 12 subtract 2x from both sides 5x - 2x = 12 3x = 12 divide both sides by 3 x = 4 now do question 2 exactly the same way. Question 3 is just the same. 6x - 8 + 2x - 5 = 7 - 2x first add all the like terms on the left so add -8 and -5 and 6x and 2x 8x - 13 = 7 - 2x get the 13 on the right by adding to both sides 8x = 7 + 13 - 2x 8x = 20 -2x add 2x to both sides 10 x = 20 divide both sides by 10 to get x on its own x = 2 Question 5 Expand the brackets first 5x + 20 = 7x - 14 now do it the same as the rest. get 20 to the right by subtracting 20 from both sides 5x = 7x -14 - 20 5x = 7x -34 get 7x on the left by subtracting from both sides 5x - 7x = -34 -2x = -34 divide both sides by -2 x = 17 you should now be able to do question 4. Hopefully this is simple enough for you to follow and will allow you to see if you understand it by following the same process to answer question 2 and 4 yourself. Goodluck
👍 50 | 👎 -20 Horsa
This is simple algebra. All you have to do is to know the value of x. 1) 5x + 3 = 2x + 15 First, we transpose. When we transpose a value, it becomes the opposite of which it was currently (If it was positive and transposed, it becomes negative, and vice versa) This becomes the result after transposing: 5x - 2x = 15 - 3 If you noticed, those with the variable (which is x) are now together and those without any variable are now together. (This is transposition.) Now, we subtract both values, thus producing this answer: 3x = 12 In order to know the value of x, we will have to divide both into 3. (3x represents 3 times x). If we divide the value of x, we will also divide the other value. By dividing them both by 3, this will be the answer. x = 4 2) 5x + 2 = x - 6 First, we transpose. 5x - x = -6 + 2 We add/subtract the values. 4x = -4 We divide both values by 4. x = -1 3) 6x - 8 + 2x - 5 = 7 - 2x This makes no difference, it's just that more values are added to the equation. First, we transpose. 6x + 2x + 2x = 7 + 8 We add/multiply these values. 10x = 15 We divide both by 10. x = 1.5 4) 9(x + 2) = 3(x - 2) With enclosed parenthesis, we will have to distribute each value. For example, 9(x + 2) In this state, we will multiply 9 by both x and 2, thus giving this answer: 9x + 18 9 times x = 9x 9 times 2 = 18 Now we continue. 3(x - 2) = 3x - 6. (Note: If you multiply 2 values which is both positive, the result will be positive. If you multiply 2 values which is both negative, the result will be positive. if you multiply 2 values when one is positive and one is negative, the result is negative.) We continue solving: 9x + 18 = 3x - 6 Transpose. 9x - 3x = -6 + 18 6x = 12 x = 2 5) 5(x + 4) = 7(x - 2) Distribute: 5x + 4 = 7x - 14 Transpose: 14 + 4 = 7x - 5x 18 = 2x Divide. 9 = x I hope this helps. Good luck on understanding it.
👍 50 | 👎 -27

If you have your own answer to the question i need help. i cant seem to get it =[?, then you can write your own version, using the form below for an extended answer.